Cell division control 42 elevates during infliximab therapy, and its increment relates to treatment response in ulcerative colitis patients. Issue 6 (9th May 2022) - Liu, Lin; Liu, Qinger; Chang, Jian; Dong, Xiaoxia; Ma, Weiping
Abstract: Background: Cell division control 42 (CDC42) regulates multiple processes of inflammation and/or immunity in autoimmune diseases and also relates to the treatment efficacy of biologic regimens clinically. This study aimed to explore the longitudinal change in CDC42 during infliximab (IFX) treatment and its correlation with IFX response in ulcerative colitis (UC) patients. Methods: Active UC patients ( N  = 48) who received IFX were recruited, and their CDC42 expressions in peripheral blood mononuclear cells (PBMCs) were detected before treatment (W0) and at 12 weeks after treatment (W12) using RT‐qPCR. Also, CDC42 in PBMCs from UC patients with remission ( N  = 20) and health controls (HCs) ( N  = 20) were detected. Results: CDC42 was reduced in active UC patients compared with UC patients with remission ( p  = 0.014) and HCs ( p  < 0.001). Besides, CDC42 was negatively correlated with CRP ( p  = 0.025), TNF‐α ( p  = 0.024), IL‐1β ( p  = 0.045), IL‐17A ( p  = 0.039), and Mayo score ( p  = 0.015) in active UC patients, but did not relate to ESR, disease duration, or IL‐6 (all p  > 0.05), while CDC42 was only negatively related to CRP in UC patients with remission ( p  = 0.046). Interestingly, CDC42 was increased at W12 after IFX treatment in active UC patients ( p  < 0.001). Specifically, CDC42 was elevated during treatment in active UC patients with IFX response ( p  < 0.001), but did not obviously change in those without IFX response ( p  = 0.061). Furthermore, CDC42 at W12 was higher in active UC patients with IFX response compared with those without IFX response ( p  = 0.049). Conclusion: Cell division control 42 serves as a potential biomarker for monitoring disease progression and IFX response in UC patients. Abstract : Active ulcerative colitis (UC) patients ( N  = 48) who received infliximab (IFX) were recruited, and their cell division control 42 (CDC42) expressions in peripheral blood mononuclear cells (PBMCs) were detected before treatment (W0) and at 12 weeks after treatment (W12) using RT‐qPCR. Also, CDC42 in PBMCs from UC patients with remission ( N  = 20) and health controls (HCs) ( N  = 20) were detected. CDC42 was reduced in active UC patients compared with UC patients with remission and HCs. Besides, CDC42 was negatively correlated with CRP, TNF‐α, IL‐1β, IL‐17A, and Mayo score in active UC patients. Interestingly, CDC42 was increased at W12 after IFX treatment in active UC patients. Specifically, CDC42 was elevated during treatment in active UC patients with IFX response; meanwhile, CDC42 at W12 was higher in active UC patients with IFX response compared with those without IFX response.